Tear film parameters in females with thyroid eye disease and diabetes: an observational study - Alanazi, Mana Alafri; Amaal Almutairi; Al-Massaad, Alanoud Abdulaziz; Baashen, Mashaaer Abdulwahhab; Almutairi, Meznah Saud; Alhssan, Abdulaziz; El-Hiti, Gamal Abdel-Rahman (Journal of the Pakistan Medical Association, 2024)
Objective: To assess different tear film parameters in female patients with thyroid eye disease and diabetes using a single portable device. Method: The observational study was conducted at the College of Applied Medical Sciences, King Saud University, Riyadh, Saudi Arabia, from January 12 to April 28, 2022, and comprised women patients with thyroid eye disease in group A, women patients with diabetes in group B, and healthy controls in group C. The participants were subjected first to the Ocular Surface Disease Index, followed by non-invasive tear breakup time, tear meniscus height, and lipid layer pattern tests using EasyTear View+. Data was analysed using SPSS 22. Results: Of the 120 women, 40(33.33%) with mean age 40.4±11.7 years were in group A, 40(33.33%) with mean age 39.8±12.2 years in group B, and 40(33.33%) controls with mean age 37.2±9.5 years were in group C. Significant differences were found in the median values of Ocular Surface Disease Index, non-invasive tear breakup time, tear meniscus height and lipid layer pattern in group C compared to groups A and B (p less than 0.001). The non-invasive tear breakup time score was strongly correlated in group B with the tear meniscus height score (r=0.559, p less than 0.001). The lipid layer pattern analysis indicated that grade A was predominant in groups A and B, while grade D was typical in group C. Conclusion: Women with thyroid eye disease and diabetes had significantly thin lipid layers and lower tear meniscus height and non-invasive tear breakup time than healthy subjects. Key Words: Dry eye syndrome, Eye abnormalities, Diabetes complications, Females, Lipids.